2021
DOI: 10.1099/mgen.0.000574
|View full text |Cite
|
Sign up to set email alerts
|

Potential syntrophic relationship between coral-associated Prosthecochloris and its companion sulfate-reducing bacterium unveiled by genomic analysis

Abstract: Endolithic microbial symbionts in the coral skeleton may play a pivotal role in maintaining coral health. However, compared to aerobic micro-organisms, research on the roles of endolithic anaerobic micro-organisms and microbe–microbe interactions in the coral skeleton are still in their infancy. In our previous study, we showed that a group of coral-associated Prosthecochloris (CAP), a genus of anaerobic green sulphur bacte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 69 publications
(112 reference statements)
3
12
0
Order By: Relevance
“…Alternatively, the syringe‐based collection method results in a homogenate of newly compromised, diseased tissue, as well as necrotic or sloughed off tissue that likely captures potential pathogen(s), organisms involved in secondary infections, or even saprophytic microorganisms proliferating off the exposed skeleton and dead coral tissue (Burge et al ., 2013; Egan and Gardiner, 2016). For example, the finding of increased Deltaproteobacteria in diseased samples of M. cavernosa and the significant enrichment of Halodesulfovibrio , known sulfate‐reducing bacteria, may have been a signature of the exposed coral skeleton (Chen et al ., 2021), or perhaps anaerobic degradation of coral tissue (Viehman et al ., 2006). Overall, the finding that disease impacts coral microbiome structure in the USVI is supported by previous findings that show shifts in coral microbiomes between healthy and diseased corals in Florida, USA (Meyer et al ., 2019; Rosales et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the syringe‐based collection method results in a homogenate of newly compromised, diseased tissue, as well as necrotic or sloughed off tissue that likely captures potential pathogen(s), organisms involved in secondary infections, or even saprophytic microorganisms proliferating off the exposed skeleton and dead coral tissue (Burge et al ., 2013; Egan and Gardiner, 2016). For example, the finding of increased Deltaproteobacteria in diseased samples of M. cavernosa and the significant enrichment of Halodesulfovibrio , known sulfate‐reducing bacteria, may have been a signature of the exposed coral skeleton (Chen et al ., 2021), or perhaps anaerobic degradation of coral tissue (Viehman et al ., 2006). Overall, the finding that disease impacts coral microbiome structure in the USVI is supported by previous findings that show shifts in coral microbiomes between healthy and diseased corals in Florida, USA (Meyer et al ., 2019; Rosales et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sulfate reducers, including Desulfobacteria , were first reported in the skeleton of Goniastrea aspera [ 101 ], but genes related to sulfur reduction were first identified in healthy and yellow bands of coral Orbicella faveolata [ 11 ]. Recently, metagenomic analysis of the skeleton of coral I. palifera and subsequent culturing and genomic analysis of dominant green sulfur bacteria (GSB) proposed a potential syntrophic relationship between GSB and SRB, where GSB can provide sulfate, which is used by SRB as an electron acceptor to generate biogenic H 2 S, which in turn is used by GSB as an electron donor [ 20 , 103 ]. In this study, MAGs belonging to the genus Chlorobium (class: Chlorobia ) and Desulfobacter (class: Desulfobacteria ) were recovered from the skeleton of P. lutea , indicating the possibility of a similar syntrophic relationship in the skeleton (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from genus Fusibacter and family Marinifilaceae, the microbiome of heat stressed A. oroides was enriched in family Clostridiaceae, order Peptostreptococcales-Tissierellales, and genera Halodesulfovibio. Genus Halodesulfovibrio has been found in corals and species from this genus seem to have antimicrobial properties (Shivani et al, 2017;Chen et al, 2021). Despite all the differences observed between studies it must be noted that observed differences may be influenced by the use of different methodologies, e.g.…”
Section: Discussionmentioning
confidence: 99%